KONSERVASI EKOSISTEM (PENGELOLAAN) MANGROVE PANTAI MUARA INDAH DI KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG - Meilinda Suriani Harefa; Cici Ariska Pasaribu; Hera Irama; Luksiade Saragih; Putri Andiana Sari; Rikardo Gultom; Sarah Rehulina Br Sianturi (Jurnal Samudra Geografi, 2023)
This study aims to find out the problems that exist in Muara Indah Beach in Pantai Labu District, Deli Serdang Regency, as well as to find out how the management (conservation) of Mangrove in Muara Indah Beach in Pantai Labu District, Deli Serdang Regency. The type of research used in this research is descriptive research. The research method in this study uses the method of directly carrying out the observation process which is followed by the research process Literature study which is a data collection method directed at searching data and information through documents, both written documents, photographs, pictures, and electronic documents that are can support in the writing process. Sources of data in this study are through literature, observation, photos, and others. The data analysis technique used in this study is through four stages, namely data collection, data reduction, data presentation and drawing conclusions. Based on research that has been carried out by several mangrove conservation efforts in Muara Indah Beach, in the District of Pantai Labu, Kab. Deli Serdang is a mangrove nursery, the nursery is carried out to overcome damage to mangrove forests due to abrasion and also deforestation of mangrove forests for land conversion. Keywords: conservation, ecosystem, mangroves.